Kill Bill. Volume 2 - Bender, Lawrence; Tarantino, Quentin; Thurman, Uma.; Carradine, David; Liu, Lucy, 1968-; Fox, Vivica A., 1964-; Madsen, Michael; Hannah, Daryl; Richardson, Robert, 1955-; Menke, Sally; Rodriguez, Robert, (Robert Anthony), 1968-; Thomas, Catherine; et al. ([United States] : Miramax Home Entertainment ; Burbank, CA : Distributed by Buena Vista Home Entertainment, 2004)
The Bride continues on her deadly pursuit of her former partners in the Deadly Viper Assassination Squad, who, in a furious assult, attempted to murder her and her unborn child on her wedding day. As the Bride faces off against allies-turned-nemeses Budd and Elle, she flashes back to the day of her deadly wedding. We learn how she was recruited and trained and about her relationship with Squad leader Bill.
Based on the character "The Bride" created by Q & U.
Special features: deleted scene; behind-the-scenes look at the making of 'Kill Bill volume 2' featuring Quentin Tarantino; 'Kill Bill volume 2' premiere - Chingon performance, bonus never-before-seen action footage.
Director of photography, Robert Richardson ; editor, Sally Menke ; original music, Robert Rodriguez and the RZA ; costume designers, Catherine Thomas, Kumiko Ogawa ; production designers, David Wasco, Cao Jui Ping.
Uma Thurman, David Carradine, Lucy Liu, Vivica A. Fox, Michael Madsen, Daryl Hannah.
MPAA rating: R; for violence, language and brief drug use.
DVD, Region 1, widescreen (2.35:1) presentation; Dolby Digital 5.1 surround, DTS, SDDS.
Keywords: Brides -- Drama; Assassins -- Drama; Training -- Drama; Asesinos -- Teatro; Feature films; Action and adventure films; Films for the hearing impaired; Suspense films